Optimized parabolic reflector antenna for Malaysia beam coverage - Fauzi, N. F. (Institute of Electrical and Electronics Engineers Inc., 2016)
Reflector antennas remain the most preferred option for satellite communication. However, some applications require the beam to be shaped precisely to the specific coverage region in order to provide high data rate services with constant signal availability. As for small region like Malaysia, it is very crucial to obtain precise beam shaping because it is located nearby other countries thus, unnecessary radiation power over undesired nearby regions shall be reduced. The shaped footprint is designed by using multi beam technique where many feed horns are employed. In previous designing, severe horn overlapping were shown and this problem has been analytically studied by the relation between the feed horn size and feed position displacement. The relation of feed horn size and feed position displacement is numerically clarified with parameter of the beam separation angle and the focal-length-to-diameter ratio (F/D) of a parabolic reflector. As a result, antenna structure for escaping feed horn overlapping are obtained.